Altitudinal differences in alpha, beta and functional diversity of an amphibian community in a biodiversity hotspot. Issue 1 (1st January 2019) - Villacampa, Jaime; Whitworth, Andrew; Allen, Laura; Malo, Juan E.
ABSTRACT: Biodiversity research along altitudinal gradients can provide us with new insights into conservation and human impacts. In this context, amphibians are a useful and important group due to their rapid response to environmental changes, severely threatened status and because of the gaps in our knowledge of their ecology, especially in tropical forests. Here, we investigate the differences in amphibian communities along an altitudinal gradient with the aim to understand how different groups respond to altitude and what factors drive such responses. We carried out our research in the Piñi-Piñi range, located in the Manu Biosphere Reserve (south-eastern Peru), a global biodiversity hotspot. We evaluated the changes in abundance, alpha, beta and functional diversity of the community with altitude along transects from 450 to 1150 m asl. We categorized species into functional groups based on their breeding sites, habitat and weight. Alpha diversity for the overall community decreased with increasing altitude, a trend partially driven by the absence of aquatic habitats in the higher elevations, which prevents colonisation by pond and stream breeders. Community composition changed with altitude and there was a low similarity between lower and higher elevations. Upper elevations were less diverse but contained species found nowhere else along the gradient, increasing the diversity of the range. Functional groups responded to altitude in different ways and several groups were absent or almost absent from the upper elevations: large species (>10 g), terrestrial, arboreal, and pond and stream breeders. Pond and stream breeders and those species found exclusively in the higher areas of the range are likely more vulnerable to habitat and climate change. Investigating the response of different functional groups and using multiple measures of diversity was useful for generating a detailed understanding of the changes in the community with altitude and their ecological and conservation implications.